Implementasi Teknologi Pengelolaan Lahan Penghasil Cabai melalui Kegiatan Budidaya dan Diversifikasi pada Masyarakat Birayang Batang Alai Selatan - Bakti Nur Ismuhajaroh; Rosalina Kumalawati; Susi Susi; Astinana Yuliarti; Karnanto Hendra Murliawan; muhammad hamid (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Management of land potential in an area requires technological innovation to produce good quality. Proper land management and processing can improve the product and standard of living of the local community. Chili commodity is a very strategic commodity, where the development of this commodity will never experience a decline and even tends to continue to be increased, due to the high level of demand and consumption. Seeing this, it is very necessary to carry out activities with the background of activities, namely 1) The local community does not realize that their area has the potential for the development of various chilies, and 2) There is still limited public knowledge regarding the use of land suitability management, cultivation technology, and post-harvest technology of various chilies. The purpose of this activity is to build community capacity by developing and utilizing the potential of both natural and human resources in order to improve the community's standard of living. The method used in the Birayang Batang Alai Selatan Village is to carry out 1) Site Surveys and Community Identification, 2) Socialization of Activity Programs, 3) Extension and Training, 4) Mentoring and Continuous Guidance. The technique used in chili cultivation is MPHP (black silver plastic mulch). Community empowerment in addition to the implementation of cultivation for women through diversification of chili-based food. The result of this activity is the achievement of maximum chili production, due to suitable land supported by appropriate technology. This technology is expected to be followed by other communities and is sustainable and more optimal which is expected to improve the welfare of the community.